IMPLEMENTASI METODE K-MEANS CLUSTERING DALAM MENGKLASTERKAN BUKU PERPUSTAKAAN DI SMK NEGERI 1 PANTAI LABU - Turiami Harianja; Hasanul Fahmi (Jurnal Sistem Informasi Kaputama (JSIK), 2022)
The development of the era of globalization in the field of technology at this time, or what is often referred to as the development of the technological industrial revolution, makes technology grow rapidly from time to time. One technology that shows development is a computerized system, which does not rule out the possibility that it will always be used in human activities. (Fahmi & Sianturi, 2019). The use of computers has penetrated almost all areas of human life today, such as in the field of education. Computer technology also plays an important role in helping humans to take important decisions such as making decisions in processing large data or what is now called Data Mining.The existence of books is very important, especially for students in schools at SMK Negeri 1 Pantai Labu. This research was conducted at SMK Negeri 1 Pantai Labu. However, to read and search for books in the Library of SMK Negeri 1 Pantai Labu, it is necessary to have a way to do clustering to make it easier to group books according to reading interests.